PREVALENCE OF SALMONELLA IN DIARRHEIC ADULT GOATS IN FIELD CONDITIONS - A. K. Mahmood; M. S. Khan; M. A. Khan; M. A. Khan; M. Bilal (Journal of Animal and Plant Sciences, 2014)
An active surveillance was undertaken to determine the prevalence of Salmonella from the diarrheic feces of adult goats, in field conditions. Salmonella is a principal cause of food-borne diseases in the world, and the most common zoonotic bacterial disease of adult goats. In this long study of one year, a total of 744/2029 cases of diarrhea were identified, which revealed an overall prevalence of diarrhea in goats to be 36.7% and salmonellosis 0.1%, with the help of commercially available API 20E kits. A significant association of a number of cases of diarrhea with the environmental temperature and humidity level of the area was established but there was no effect of season, temperature or humidity levels with the prevalence of salmonellosis in the area. Open grazing was a common practice and the animals would eat garbage, grass, leaves and drink standing water, available to them. The detection of Salmonella species in feces, from field conditions, needs special attention to prevent an outbreak in animal and human population in the area.
Keywords: Prevalence; Salmonella; diarrhea; adult goats